Khosois al-Haj 'Abd Al-Malik ibn Karim Amrullah (HAMKA) Al-Adabiyah fi Riwayah ‘Adalah Ilahiyah - Rijal Mahdi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2019)
This study aims to identify the characteristics of the great Indonesian literary work Haji Abdul Malik bin Karim Amrullah (Hamka) in his novel ‘Keadilan Ilahi’ (Divine Justice), this work is one of the literary heritage of the old Indonesian poet that is rarely found by readers of Indonesian literary works in libraries throughout the Malay Islands, especially in Indonesia. Specifically, this research attempts to explain the characteristics of Hamka's literature, which is represented in narrative language and in a very subtle and directed language style when raising the theme of his novel. The importance of this research is because of the knowledge of the unique techniques possessed by Hamka in writing this novel, this work is no less flashy and prestige than the work of other novels such as ‘Tengelamnya Kapal Van der Wijck’ (Sinking of the Van der Wijck) and ‘Di bawah Naungan Ka’bah’ (Under the Protection of the Kaaba). This study uses literary analysis methods that examine narrative techniques, dialogue, internal dialogue, retrieval, message delivery, and monologues used by Hamka in his novels. The second is to study Hamka's techniques in the novel by presenting parts of novel texts in Indonesian and providing the proposed Arabic translation.